Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd007536
|View full text |Cite
|
Sign up to set email alerts
|

Routine pre-pregnancy health promotion for improving pregnancy outcomes

Abstract: Background-A number of potentially modifiable risk factors are known to be associated with poor pregnancy outcomes. These include smoking, drinking excess alcohol, and poor nutrition. Routine health promotion (encompassing education, advice and general health assessment) in the pre-pregnancy period has been proposed for improving pregnancy outcomes by encouraging behavioural change, or allowing early identification of risk factors. While results from observational studies have been encouraging, this review exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…18-23 PCC has shown promise in promoting healthy prepregnancy behaviors and even affecting birth outcomes in mothers with chronic disease. 24,25 However, though PCC is recommended for all women of childbearing age, 26 studies estimate that only 30% of women receive PCC during the 12 months before pregnancy. 13 …”
Section: Introductionmentioning
confidence: 99%
“…18-23 PCC has shown promise in promoting healthy prepregnancy behaviors and even affecting birth outcomes in mothers with chronic disease. 24,25 However, though PCC is recommended for all women of childbearing age, 26 studies estimate that only 30% of women receive PCC during the 12 months before pregnancy. 13 …”
Section: Introductionmentioning
confidence: 99%
“…The shift is also based on a growing body of evidence that women’s preconceptional health affects pregnancy-related outcomes including birthweight, fetal growth, and pregnancy weight gain and its sequelae (Institute of Medicine [IOM], 2009; Weisman et al, 2009, 2010). To date, however, few preconceptional interventions have been subjected to rigorous testing, and there is little evidence of the effectiveness of pre-pregnancy health promotion programs (Korenbrot, Steinberg, Bender, & Newberry, 2002; Wahabi, Alziedan, Bawazeer, Al-Ansary, & Esmaiel, 2010; Whitworth & Dowsell, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Although routine preconception care, including reproductive life planning, could theoretically reduce unintended pregnancy and improve pregnancy and birth outcomes, there is very little research to date in this area. A 2009 Cochrane review concluded that, because of a paucity of research, there is little evidence for the effectiveness of prepregnancy health promotion (Whitworth & Dowswell, ). In the current climate of rising healthcare costs, there is growing pressure from both public and private sectors to establish evidence for the cost‐effectiveness and efficacy of interventions (Johnson et al., ).…”
Section: The Future Of Preconception Carementioning
confidence: 99%